Türk Musikisi Ses Sisteminin Xx. Yy Başlarından Günümüze Gelişinin Karşılaştırmalı İncelenmesi - Ergöz, Hatice (Sosyal Bilimler Enstitüsü, 1994)
9. yüzyıldan bu yana Klasik Türk Müziği nazariyatı ve ses sistemimiz üzerine pekçok müzikolog çalışma yapmıştır. 9. yy'da Farabi tarafından başlatılan bu çalışmalar 13. ve 15. yy'larda Safiyüddin ve Meragalı Âbdülkadir tarafından devam ettirilmiştir. Bunu izleyen yüzyıllarda başka bazı nazari eserler yazılmıştır. Ancak Meragalı Âbdülkadir 'den sonra bu yön deki çalışmalara ait bir belgeye rastlanmamıştır. Zaten bu eserler el yazması oldukları için yayılmamışlardır., Bu durum 19. yy 'a dek sürmüştür. Bu yüzyılın 2. yarısında Klasik Türk Müziği nazariyatına bağlı çalışmalar gelişmiş ve edvarların basımı mümkün olmuştur. Haşim Bey tarafından yazılan mecmua bunlardandır. Bu eser, Sultan Abdülaziz'e sunul muştur. Eserde mûsikî hakkında yer alan genel bilgiler dışında, makamların seyir ve karakterleri incelenmiş tir. Bu kitaplarla bilgilenen ve Klasik Türk Müziğiyle ilgilenen müzikologlar, karşıt görüşlerini söylemeye başlamışlardır. Müziğimizin özellikle bilimsel yanı üzerinde durulmuş, fiziksel ve matematiksel temeller aranmıştır. Galata Mevlevihânesi şeyhi Ataullah Efendi, Yenikapı Mevlevihânesi Şeyhi M.Celâleddin Dede Efendi ve Bahariye Mevlevihânesi Şeyhi Hüseyin Fahreddin Dede bu çalışmaların öncüleri olmuşlardır. Bu müzisyenler bilgilerini öğrencilerine vererek gelişmeyi başlatmış lardır. İlk bilimsel çalışma ise Rauf Yekta Bey tarafından başlatılmıştır. Gerek kitaplarıyla, gerekse dergi ve makâlelerdeki yazılarıyla müziğimizi düzensizlikten kurtarmaya çalışmıştır. Başlattığı çalışmalar Arel, Ezgi ve Uzdilek tarafından hız kazandırılmış ve bir sistem içine yerleştirilmiştir. Bugünkü sistem, 24 eşit olmayan aralık ve 25 ses içerir. Arel, Ezgi ve Uzdilek sistemi olarak adlandırı lır. Bu yüzyılda Karşıt görüşlerini söylemiş Arel, Ezgi, Uzdilek dışında pekçok müzisyenimiz vardır. Bir oktavı değişik yollarla bölen bu nazariyeler yayılamamış ve yalnızca bilgi olarak kalmışlardır. Bunlar; E.KARADENİZ ye A.TÖRE'ye ait 41 aralıklı dizi temeline dayanan nazariye ve Kemal İLERİCİ, Ayhan - v - ZEREN ve M.Niyazi AYOMAK'a ait eşit aralık temeline dayanan nazariyelerdir. Ayrıca yakın zamanlarda Yalçın TURA'nın geleneksel sistem hakkındaki çalışması ve Erol SAYAN 'in 35 eşit olmayan aralık 36 ses temeline dayanan çalışması da konuyla ilgili karşıt görüşlerdir. Tez tüm bu nazariyeleri birarada vermekte ve bunları karşılaştırmaktadır. Özellikle logaritma ve sent hesaplarının bulunmasıyla hızlanan bu nazariyelere tezimde ayrı ayrı değineceğim.

Since the Nmeth Century many a musicologist executed a lot of researches on Classical Turkish Music and our sound systems. These studies initiated by Farabi in the 9th. Century vere taken over by Safiyuddin and Abdulkadir of Meraga in 13th and 15th Centuries respectively. In the course of following Centuries, some other theoretical works were composed. Nevertheless, there has been no documentary foundings following the work of Abdulkadir from Meraga. On accounts that most of the works were handwritten, possibility of their circulation were slim. Such hadicap was continued until 19th Century. In the second half of this Century theoretical works relating to calssical Turkish music were developed and periodicals covering classical Turkish music were to find opportunity of being published. The periodical written and published by Haşim Bey is one of these. This work was submitted to Sultan Abdulaziz. In addition to general information about the music, the work also included studies involving flow and characteristics of the melodies as well as their affinity and relationships to the Western music. Our musicologist being enlightened with these - vii - written works and become interested in theory of classical Turkish music begun rendering their own ideas. Especially the scientific side of our music was scrutinized, physical and mathematical roots were searched through it. The sheikh of Galata lodge of Mevlevi dervishes Ataullah Efendi, the sheikh of Yenikapi lodge of Mevlevi dervishes Celaleddin Dede Efendi and, the sheikh of Bahriye lodge of Mevlevi dervishes Hüseyin Fahrettin Dede were path-breaking fine musicians promoting these studies, and transmitted their knowledge to the following progeny of followers.' The initial scientific work bears the signature of Rauf Yekta Bey, Either by his books or by magazines and articles he exploited ways and means to establish a well founded order in our musical tradition. Thanks to immaculate achievements of Arel, Ezgi and Uzdilek, his prime studies were endowed with progress, and established in an order. Today's system is comprised of 24 unequal intervals and 25 sounds. It is named as Arel, Ezgi, and Uzdilek System. There are many other national musicians of quality in this Century other than Arel, İzgi, and Uzdilek, having voiced their ideas. These theories dividing an actave in different ways are listed as follows ; The theory based on 41-intervals scale pertaining - vxxi - to E.Karadeniz and A. Töre, the theory of Kemal İlerici, Ayhan Zeren, Mildan Niyazi Ayomak having 53 matching intervals. Erol Sayan's theory of 35 unequal intervals and 36 sounds, and the theories of traditional systems. We may briefly mention these as; Rauf Yekta' s 24- intervals scale found its roots way back in Farabi. This scale have three different sounds comprized of 8/9 of major key tone, 9/10 of minor key tone, and 15/16 half major key tone. It is "the perfect immortal system" as the Greeks called it, which is for us simply an unimpressing scale, one of the oldest makams, beginning Yegâh. Arel, Ezgi, and Uzdilek System is progressed and further matured by sciertific studies through basics laid oft by Rauf Yekta, Notably, H. Saadettin Arel has contributed to widespread development of the system with his work and magazines. Even today this system is accepted theoretically, albeit, it has undergone some change in performance. As the main scale Çargâh was taken as a model which also fits the Western Major key. Mildan Niyazi championing the system that was structured over 53 equal intervals scale, used Çargâh scale scale as the starting point and searshed for ways and means to deliver our music from equivocal values. Names and standing points of the motes were marked by consonants named as "musical numbers". Kemal İlerici and Ayhan Zeren, on the other hand, - xx were followers of 53 equal-temperaments and conducted different studies. Kemal İlerici has taken Hüseyni scale as a basis and combined all the other tessitura within the formation of this scale, and focused his attention on harmonizing of our tessitura. Ayhan Zeren, applied the scale of which he is obtained by means of multiplying fives and fours to 53- equal temperaments, however, he accepted it as a scale made of 24 intervals and 25 sounds. The study realized by Töre and Karadeniz, nevertheless, is based on a system with 41-intervals. Because of the main scale is appropriate to diatonic scale intervals of the Western music, it is Rast scale. In place of the Rast note, sol sound is used. The sounds are obtained by means of sent system of fives and fours intervals. Owing to we have no written source other than his brochures issued, we learnt that Erol Sayan one of the instructors of ITU School of Turkish Music, used a scale comprised of 35 intervals-36 sounds and a micro analysis. Other than all these, in the period of Safiyuddin, Farabi and the others, we encounter the traditional system comprised of 17-18 sounds used with our bağlama (the folk instrument with three double strings) pitch of notes. Again according to his - x - researches, ITU STM Lectures Yalçın Tura has come to the conslusion it is a must that this system ought to be taken as basics and evaluated contemporarily. The treatise shall look into all the above concerns in detail
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Sosyal Bilimler Enstitüsü, 1994
Thesis (M.A.) -- İstanbul Technical University, Institute of Social Sciences, 1994
Keywords: Müzik; Sanat müziği; Ses sistemleri; Türk sanat müziği; Music; Art music; Sound systems; Turkish art music